Building a Nation Branding Image through Social Media Strategy: What does Gen Z say? - Ade Pranajaya; Sara Rashid (Universitas Pendidikan Nasional, 2025)
This study explores how digital diplomacy, particularly through digital content and social media campaigns, impacts Indonesia’s nation brand image in Pakistan, with cultural curiosity among Pakistani Gen Z acting as a mediating factor. Using a quantitative research approach, data were gathered from 545 respondents selected via purposive sampling and analyzed with Structural Equation Modelling. The results show that digital content and social media campaigns do not directly improve Indonesia’s nation brand image. Instead, both significantly increase cultural curiosity among Gen Z audiences. An important insight is that cultural curiosity effectively mediates the relationship between social media campaigns and the nation's brand image, while digital content has no significant effect. This indicates that successful digital nation branding relies on culturally engaging social media campaigns that foster familiarity and meaningful cognitive connections. Theoretically, the study advances the literature on nation branding and digital diplomacy by identifying cultural curiosity as a key psychological mechanism linking diplomatic stimuli to brand outcomes, supporting the Stimulus–Organism–Response (S–O–R) framework and consumer multiculturation theory. Future research should incorporate mixed and experimental methods, expand to broader contexts, and use applied behavioral and participatory data to capture genuine digital diplomacy engagement better. Overall, the study highlights the strategic importance of digital diplomacy in sparking curiosity and shaping positive international perceptions among younger audiences.